Development of Integrated Teachings of Al-Qur'an Verses in Class I Students in Elementary Schools - Mutmainna Mutmainna (Pedagogik Journal of Islamic Elementary School, 2020)
The purpose of this study was to develop a prototype of integrated five-senses teaching material in the verses of the Qur'an in class I students at SDN 01 Lalebbata Palopo, and to find out the level of effectiveness of teaching materials developed towards the learning outcomes of class students I at SDN 01 Lalebbata Palopo. Research & Development is the research method used. To develop products, this study uses a 4-D development model consisting of four stages, namely: (1) Define, (2) Design, (3) Develop, and (4) Disseminate. Data collection techniques used are documentation, observation, and validation. The data analysis technique used by the researcher was to test its validity by using the Aiken's formula and observation using descriptive statistical analysis. By the results of the validation, the integrated five-sensory material module with the verses of the Qur’an is said to be valid because it obtains an average validation result of 0.67 where the value is included in the valid category in terms of all aspects of the module. This module is said to be effective using the student activity observation sheet, where the results of the observation sheet which is 93.10% fall into the very good category.